(3GdRjLs - (3YHO GdbGOQ Hf UaGFj GdehUdjs
(3ChdgG (B:s
(3GdMeO ddg GdPi djS dg THjg hdGeKGd hHYO , ajbhd GdehUdi ehdOkG heScfkG YHO GdbGOQ Hf UaGFi , Efi cfJ eTJZdkG HJMUjd Yde GdgjFI HQgI ef GdReGf , Ke EfJbdJ efg Edi Yde GdRjLGJ s
(3BNQgG (B:s
(3hGYde Cf eWGdY GdHQhL eeG jJhba YdjgG CcKQ GdCYeGd ai gPG Gdaf , EPG jJhba YdjgG hCYeGQ GdehGdjO hefgG JLfi GdCKeGQ , hJYQa GdCYeGQ hdgPG CaQOJgG hLYdJgG ebGdI KGdKI hGddg Gdehab dcd NjQ s
(3Cdag GdeDda dMSjf Hf ESeGYjd HGTGs
(3HgG fXGe GdJYbjHIs
(3HgG LOGhd HChdgG hba eDQN SfI (B1192(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs